Knowledge Level of Dribbling in the SSB U-17 Youth Generation Football Game Until 2024 - Sembiring, Andi Suhendra; Hendrawan, Dicky (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
This research aims to determine the level of knowledge of dribbling the ball in the 2024 SSB U-17 Young Generation Sampali football game. The subjects in this research were all 20 U-17 SSB U-17 Young Generation Sampali players. The design in this study uses quantitative descriptive, namely regarding the level of dribbling knowledge of each player, meaning that in this study the researcher only wants to know the level of dribbling knowledge of the U-17 SSB Sampali Young Generation soccer players in 2024, where the data is in the form of numbers. The instrument in this research uses an objective test in the form of multiple choice questions containing the meaning and techniques for implementing dribbling, which consists of the understanding and techniques for implementing dribbling. Other factors are the benefits of dribbling and external supporting factors. From the results of the research and discussion, it can be seen that the level of dribbling knowledge in the 2024 SSB U-17 Young Generation soccer game is in the low category at 55%, the medium category at 45%, and the high category at 0%. Thus, the conclusion from the research that has been carried out is that the level of knowledge of dribbling the ball in the 2024 SSB U-17 Young Generation Sampali football game is in the low category, namely 55%. The level of dribbling knowledge consists of 2 categories, from each category it can be concluded that: (1) Understanding of the meaning and techniques for implementing dribbling among SSB U-17 Sampali Young Generation soccer players in 2024 is in the low category, namely 55%. (2). Understanding of the benefit factors and supporting factors for the 2024 SSB U-17 Young Generation soccer players is in the medium category, namely 40%.